Chronic Hyperglycemia Modulates Rat Osteoporotic Cortical Bone Microarchitecture into Less Fragile Structures - Cristina de Mello-Sampayo; Alaíde Alves Agripino; Duarte Stilwell; Bruno Vidal; Ana Luisa Fernando; Beatriz Silva-Lima; Maria Fátima Vaz; Helena Canhão; M. Cristina Marques (International Journal of Endocrinology)
There is controversy concerning the diabetes impact on bone quality, notorious in type 2 diabetic postmenopausal women. One pointed cause might be uncontrolled glycemia. In this study, the effect of chronic hyperglycemia in bone turnover, morphology, and biomechanics was evaluated in female Wistar rats in the presence/absence of estrogens (ovariectomy). Animals (n=28) were divided into sham, ovariectomized (OVX), hyperglycemic (streptozotocin 40 mg/kg, single-dose i.p.-STZ), and hyperglycemic-ovariectomized (STZ + OVX) animals. Blood biomarkers were estimated 60 days postovariectomy. Body weight, vertebral microarchitecture (L4-histomorphometry), femur biomechanical properties (bending tests), tibia ultrastructure (scanning electron microscopy), and femur and urinary calcium (atomic absorption) were also evaluated. The increased PINP/CTX ratio of hyperglycemic animals and the similar ratio between STZ + OVX and healthy animals contrasting with the lower ratio of OVX (in line with its histomorphometric data) suggest a tendency for improved bone formation in hyperglycemic-ovariectomized animals. The increased tibia medullar canal, which contrasts with the unaffected cortical thickness of both hyperglycemic groups while that of OVX decreased, was associated to the increased stiffness and strength of STZ + OVX bones compared to those of OVX, in line with the observed ultrastructure. Concluding, chronic hyperglycemia in ovariectomized female rats causes bone morphological changes that translate positively in the ultrastructure and mechanical properties of cortical bones.